The ex-Casa del Fascio in Predappio and the question of the "difficult heritage" of Fascism in contemporary Italy. Issue 2 (19th March 2019) - Storchi, Simona
Abstract : This article focuses on the history and reception of the ex-Casa del Fascio in Predappio, from the end of the Second World War to the current plans for its restoration and reuse as a study centre and a museum of Fascism. Taking into account changes in legislative, political, and cultural contexts, the article proposes an approach to the legacy of Fascist architecture in Italy based not just on its ideological charge, but also on cultural and political shifts, changes in legislation, and the complex relationships between the bodies in charge of the preservation and management of public heritage. The recent plans put forward by the town administration to restore the building and turn it into a museum of Fascism have reopened the debate on the heritage of Fascism and the ex-Casa del Fascio has now become one of the most conspicuous emblems of Italy's uneasy relationship with its Fascist past and of the problems of dealing with the material legacy of the Fascist regime. Italian summary: L'articolo traccia la storia dell'ex Casa del Fascio di Predappio dalla fine della seconda guerra mondiale al recente progetto di riutilizzo dell'edificio come sede di un centro di documentazione e museo del fascismo. Si propone un approccio alla questione delle difficoltà di gestione del patrimonio architettonico dell'era fascista che tiene in considerazione non solo il portato ideologico degli edifici in questione, ma anche i cambiamenti politici, culturali e legislativi nell'Italia del dopoguerra, oltre che i complessi rapporti fra i vari enti incaricati della conservazione e della gestione del patrimonio architettonico. Si analizza infine la ricezione mediatica della proposta di un museo del fascismo a Predappio, evidenziando come la questione dell'eredità materiale del regime fascista sia a tutt'oggi di difficile risoluzione.